London's Urban Landscape Another Way of Telling (University College London, 2019)
London's Urban Landscape is the first major study of a global city to adopt a materialist perspective and stress the significance of place and the built environment to the urban landscape. Edited by Christopher Tilley, the volume is inspired by phenomenological thinking and presents fine-grained ethnographies of the practices of everyday life in London. In doing so, it charts a unique perspective on the city that integrates ethnographies of daily life with an analysis of material culture. The first part of the volume considers the residential sphere of urban life, discussing in detailed case studies ordinary residential streets, housing estates, suburbia and London's mobile 'linear village' of houseboats. The second part analyses the public sphere, including ethnographies of markets, a park, the social rhythms of a taxi rank, and graffiti and street art. London's Urban Landscape returns us to the everyday lives of people and the manner in which they understand their lives. The deeply sensuous character of the embodied experience of the city is invoked in the thick descriptions of entangled relationships between people and places, and the paths of movement between them. What stories do door bells and house facades tell us about contemporary life in a Victorian terrace? How do antiques acquire value and significance in a market? How does living in a concrete megastructure relate to the lives of the people who dwell there? These and a host of other questions are addressed in this fascinating book that will appeal widely to all readers interested in London or contemporary urban life.